Learning Management Strategies Based on Multiple Intelligences to Optimize Children’s Potential: Systematic Review 2015-2024 - Amini, Amini; Abdulkadir, Abubakar (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
The implementation of multiple intelligences theory in educational settings remains inconsistent despite growing recognition of diverse learning needs among children. This systematic literature review aims to analyze learning management strategies based on multiple intelligences for optimizing children's potential during 2015-2024. Following PRISMA guidelines, we systematically searched five databases (Scopus, Web of Science, ERIC, ProQuest, Google Scholar) using predetermined keywords, yielding 45 eligible studies after rigorous screening. Results reveal three primary strategy clusters: differentiated instruction approaches, assessment diversification methods, and collaborative learning frameworks that accommodate linguistic, logical-mathematical, spatial, kinesthetic, musical, interpersonal, intrapersonal, and naturalistic intelligences. Findings indicate significant positive impacts on student engagement, academic achievement, and holistic development when educators implement integrated multiple intelligences-based management strategies. This review provides practical implications for educational leaders and practitioners in designing inclusive learning management systems that recognize and nurture each child's unique intelligence profile, ultimately contributing to more equitable and effective educational practices.